The indefinite integral above is equal to
for constants and , where denotes the arbitrary constant of integration. Find the value of .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Dividing the numerator and the denominator of ( cos 3 x + sin 3 x ) 2 sin 2 x cos 2 x by cos 6 x , we obtain the expression ( 1 + tan 3 x ) 2 tan 2 x sec 2 x .
Then I = ∫ ( sin 3 x + cos 3 x ) 2 sin 2 x cos 2 x d x = ∫ ( 1 + tan 3 x ) 2 tan 2 x sec 2 x d x = 3 1 ∫ ( 1 + tan 3 x ) 2 d tan 3 x = − 3 ( 1 + tan 3 x ) 1 + C . Multiplying the last fraction by cos 3 x cos 3 x , we get that I = − 3 1 cos 3 x + sin 3 x cos 3 x + C . Factoring the denominator and using the identity sin 2 x + cos 2 x = 1 we get that I = − 3 1 ( cos x + sin x ) ( cos 2 x − sin x cos x + sin 2 x ) cos 3 x + C = − 3 1 ( cos x + sin x ) ( 1 − sin x cos x ) cos 3 x + C . Therefore, A = B = 1 . So the answer is A + B = 2 .